The effects of NCCC Care's educational assistance among it's grantees a study of five selected cases - Capili, May Che B.
Five randomly selected cases of college grantees of NCCC Cares' Educational Assistance Program were presented to determine the extent of effect of the program. Program evaluation was determined through these four grantees' Measures: 1) Grantee Selection, 2) Grantees' Academic Performance, 3) Effects of Program Components, and 4) Parent Perception. Qualitative data were gathered through in-depth interviews. The program guidelines and requirements and the changes incorporated were also reviewed. The three components of EAP namely: Tutorials, Values Formation and Counseling were explored to know how these components have an effect on the grantees' performance. Grantees' grades prior to availing and through the course of the grant were also considered to fully determine the extent of effect of the program on grantees' academic achievement . Also the appraisal system by means of giving out of incentives was added as one indicator of effect.. These measures enabled the proponent of this study to determine the effects of the Corporate Social responsibility of the Educational Assistance program of NCCC Cares to its grantees. Grantees' Measure enabled the analysis of narratives in determining similarities and important insights of the program's outcome. The study shows that the assistance offered by the program could either motive the grantees to strive more or be lax since no grade requirement is needed. The Performance Appraisal System, giving incentives in the form of gift certificates to students who performed well in their studies to motivate grantees to perform well in their studies. It also showed that EAP created the impact not only on the grantees academic performance but also other student , such as retention, persistence and increased options for college education. The three program components were instrumental in developing capability and responsibility to its grantees. However, factors such as family problem and adjustment on new environment inadvertently affect student performance. The program with the aim of catering more students to the program did not require cut-off grade in applying for the program. It caused the foundation to change the name of the recipients from 'scholars' to 'grantees'. One grantee pointed out that could have an effect on grantees' performance since the term scholars connote a higher and strict grade requirement. In conclusion, two (2) valuable variables in determining program effectiveness are highlighted: 'Quality of interaction.' These are important to grantees' perception of effectiveness in the implementation of the EAP's objectives. Interaction and communication particularly with the staff affects the grantees in varying levels.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication